Direct laboratory evidence that pregnancy-induced hypertension might be associated with increased catecholamines and decreased renalase concentrations in the umbilical cord and mother's blood - Baykus, Yakup; Ustebay, Sefer; Deniz, Rulin; Ugur, Kader; Yavuzkir, Seyda; Aydin, Suleyman (Walter de Gruyter Gmbh, 2019)
Background: Renalase (RNL) is a controversial enzyme as to whether it oxidizes catecholamines (CAs) (as is generally accepted) in the blood or not. CAs (dopamine [DPMN], epinephrine [EPI] and norepinephrine [NEPI]) are associated with hypertension, including pregnancy-induced hypertension, which occurs in 8-10% of all pregnancies. Therefore, the aim of the study was to compare CAs and renalase concentration in (i) normotensive controls (C), (ii) patients with preeclampsia (PE) and (iii) patients with severe preeclampsia (SPE), which is one of the well-known symptoms of hypertension. Methods: This case-control study involved 90 women divided into three groups - 30 C, 30 PE and 30 SPE - whose age and body mass indexes (BMIs) were similar. A total of 270 blood samples (90 maternal samples, 90 umbilical cord artery samples and 90 umbilical cord vein samples) were obtained. CAs and RNL concentrations of the biological samples were measured by enzyme-linked immunosorbent assay (ELISA). Results: Comparing the amounts of CAs, RNL and systolic blood pressure (SBP)/diastolic blood pressure (DBP) between healthy control pregnant women and pregnant women with PE and SPE (SBP/DBP was 120/80 mm Hg for C, above 140/90 mm Hg for PE and above 160/110 mm Hg for SPE), the levels of CAs were significantly increased whereas RNL was reduced. The correlation between SBP/DBP and the amount of RNL in pregnant women with PE and SPE was negative. Conclusions: These novel results are evidence that hypertension seen in PE and SPE is directly related to increased levels of CAs and reduced RNL concentrations. The use of RNL preparations may be preferred in future to prevent maternal and perinatal morbidity and mortality due to pregnancy-induced hypertension.
Keywords: catecholamines; hypertension; pregnancy; renalase